2006
DOI: 10.1007/s11095-006-9129-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size and Compression Force on Compaction Behavior and Derived Mathematical Parameters of Compressibility

Abstract: Values of Py, 1/b, and tau0' obtained from Heckel, Kawakita, and Adams equations, respectively, can be interpreted as a measure of single particle nominal fracture strength during confined compression loading. Walker and Adams parameters were less affected, than Heckel and Kawakita parameters, by the applied pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 32 publications
4
72
0
1
Order By: Relevance
“…Elastic recovery is the reversible part of deformation and is indicative of poor interparticulate bonding (14,31). In this study, it was observed that the elastic recovery of each particle-size fraction increased with increasing compression pressure, which was already observed by Patel et al (14).…”
Section: Compactibility and Elastic Recoverysupporting
confidence: 79%
See 1 more Smart Citation
“…Elastic recovery is the reversible part of deformation and is indicative of poor interparticulate bonding (14,31). In this study, it was observed that the elastic recovery of each particle-size fraction increased with increasing compression pressure, which was already observed by Patel et al (14).…”
Section: Compactibility and Elastic Recoverysupporting
confidence: 79%
“…For example, it has been shown that the fragmentation propensity of a substance under load increases with its particle size (3,14). For this reason, a change in the mean particle size may alter the predominant consolidation mechanism.…”
mentioning
confidence: 99%
“…The constant "a" is related to the total volume reduction for the powder bed (compressibility index) and the constant "b" is related to the resistant forces (friction/cohesion) to compression. 9) Particle Size Samples were fractionated on a ROTAP sieve shaker (RX29, W.S. Tyler Co., Mentor, OH, U.S.A.) using stainless steel 420, 250, 180,125 105, 75 mm sieves, stacked together in the order written (Fisher Scientific Co., Pittsburgh, PA, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…However, in 1982 a study by McKenna and McCafferty [17] revealed that during their calculation of yield pressure, particle size was irrelevant for lactose. Another study by Patel et al [18] found that the yield pressure of paracetamol was dependant on particle size, where increasing particle size resulted in higher yield pressure values. Recent studies have suggested that as the yield pressure is derived from the density pressure relationship this value is actually an indication of powder densification rate that may be effected by particle size [19].…”
Section: Introductionmentioning
confidence: 98%